Seed Borne Fungal Diseases of Fruits in Mymensingh District - Rashid, AQM B; Meah, MB; Sultana, A (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted to evaluate the major seed borne fungal diseases of fruits in Mymensingh. Being perishable crop the fruits were found easily prone to the attack of various disease causing organisms at almost all sphere of their production practices from orchard to the storage, transit and consumption. Fruit rot (Botryodiplodia theobromae) and anthracnose (Colletotrichum gloesporioides) were found as the most common and serious diseases in many fruits such as mango, guava, banana, papaya, pineapple etc. Prevalence of the diseases, losses incurred and probable control measures have been suggested in most of the cases. J. Environ. Sci. & Natural Resources, 8(1): 153-156 2015